Study of the photodegradation of a fragrance ingredient for aquatic environmental fate assessment. (April 2017) - Lin, Jianming; Emberger, Matthew
Abstract: Photodegradation is an important abiotic degradation process to be taken into account for more accurate assessment of the fate of chemicals in the aquatic environment, especially those that are not readily biodegradable. Although the significant role of indirect photodegradation in the environmental fate of chemicals has been revealed in recent research, because of the many confounding factors affecting its kinetics, no straightforward approaches can be used to investigate this degradation process for environmental fate assessment. The indirect photodegradation of a fragrance ingredient named Pamplewood was studied in this work for its fate assessment. Indirect photodegradation rates under various indoor and outdoor conditions were measured by using an LC-MS method. Although the half-lives varied from 4 to 13 days, they collectively indicated that Pamplewood is intrinsically photolabile and can undergo rapid photodegradation. Results from quencher experiments revealed that ⋅OH was the main reactive intermediate responsible for indirect photodegradation, with a half-life of about 18 days in sunlit surface water, based on the experimentally determined second-order rate constant (8.48 ± 0.19 × 10 9  M −1  s −1 ). Photodegradation products of Pamplewood were also studied by GC-MS, LC-MS and total organic carbon content analyses. The results indicated that intermediates of Pamplewood photodegradation continued to photodegrade into smaller and more polar species. Complete mineralization of Pamplewood was observed when it was reacted with hydroxyl radicals in an aqueous solution. This novel approach can be applied for a more realistic environmental fate assessment of other non-readily biodegradable, hydrolysis-resistant, and non-sunlight-absorbing fragrance ingredients. Graphical abstract: Highlights: Indirect photodegradation of Pamplewood was estimated to be about 18 days. Reaction with hydroxyl radicals is the mechanism for the indirect photodegradation of Pamplewood. Indirect photodegradation of Pamplewood is expected to eventually lead to complete mineralization.